Analyzing the Success Rate in the Subject of Cost Accounting - Ángel Tejada Ponce; Rosario Pérez Morote; Yolanda Ramírez Córcoles; Francisca Tejedo Romero; Carolina Pontones Rosa (Universitat Politècnica de València, 2012)
The implementation of the European Higher Education Area in Spain has involved a substantial change in the traditional practices of university education, introducing important modifications both in the teaching methodology and in the assessment criteria. This work presents the experience carried out by the Faculty of Economics and Business Administration of Albacete in the subject of Cost Accounting. The paper aims to determine whether the new methodologies used in recent years and the introduction of new criteria for assessment have had a positive impact on the improvement of the students' performance and motivation in the aforementioned subject, which is taught in the third year of the degree in Business and Management Administration (ADE). In order to achieve this, we compared the grades obtained by students during the academic years 2009/2010 and 2010/2011 (in which the ECTS methodology was applied) with those obtained in the two immediately preceding academic years: 2007/2008 and 2008/2009 (where the teaching methodology involved lectures and a final exam worth 100% of the final grade). The findings evince an overall increase in the rate of students who take the exam and participate in the process of continuous assessment as a result of the new teaching methodologies.